2020
DOI: 10.1111/ced.14425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum cardiac troponin I and N‐terminal pro‐B‐type natriuretic peptide levels in patients with alopecia areata

Abstract: Alopecia areata (AA) is a recurrent, immune-mediated, hair-loss disorder. It is associated with other autoimmune disorders that carry a high risk of cardiovascular disease (CVD). However, there is a lack of reports on the association of cardiovascular comorbidities and AA. Cardiac troponin I is a biomarker of myocardial ischaemia and inflammation, while N-terminal pro-B-type natriuretic peptide is used in the diagnosis of congestive heart failure. This study was conducted to assess the serum level of both mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…(2020) in Egyptian patients reported significantly elevated levels of cardiac troponin I and N-terminal pro-B-type natriuretic peptide biomarkers in patients with AA compared with controls. The study suggested a possible association of AA with myocardial inflammation and an increased risk of developing cardiovascular disease [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2020) in Egyptian patients reported significantly elevated levels of cardiac troponin I and N-terminal pro-B-type natriuretic peptide biomarkers in patients with AA compared with controls. The study suggested a possible association of AA with myocardial inflammation and an increased risk of developing cardiovascular disease [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recently, in alopecia areata, literature data show a tendency to thrombosis and an increased risk of heart attack and stroke. In addition, studies have found elevated levels of cardiac biomarker troponin I and congestive heart disease biomarker BNP in patients with alopecia areata [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…AA is an inflammatory form of nonscarring alopecia, which can affect any hair-bearing area. 42 Clinical presentations can include the sudden onset of round alopecic patches to total scalp and body hair loss, known as alopecia totalis and universalis, respectively. 43,44 AA affects both men and women of all ages, with an estimated lifetime risk of 2.1% in the general population.…”
Section: Aamentioning
confidence: 99%
“…57 Further supporting this finding, a case-control study found that serum levels of cTnI (mean difference = 48.77; 95% CI: 46.2-51.33) and N-terminal pro-B-type natriuretic peptide (NT proBNP) (mean difference = 30.87; 95% CI: 28.41-33.33) were significantly higher in patients with AA compared to controls (cTnI t(86) = 37.79; p < 0.001, NT proBNP t(86) = 24.97; p < 0.001). 42 Although many studies have reported a correlation between AA and CVD risk, there have been a few studies that potentially counter this claim. In a retrospective study of 1377 patients with AA over a 10-year period, Huang et al found patients with AA had decreased odds of developing stroke (OR: 0.39; 95% CI: 0.18-0.87) and a trend towards decreased AMI (OR: 0.91; 95% CI: 0.59-1.39).…”
Section: Aamentioning
confidence: 99%
See 1 more Smart Citation